IMPLEMENTASI SISTEM E-BERPADU DI PENGADILAN NEGERI PONTIANAK KELAS 1A - NIM. A1012201170, RASENDRIYA CLARISYA (Jurnal Fatwa Hukum, 2025)
Abstract  This research aims to analyze the implementation of the E-Berpadu System (Integrated Electronic Criminal Files) at the Pontianak District Court Class 1A, which is a digital innovation by the Supreme Court in the context of modernizing the criminal justice system. E-Berpadu is designed to enhance the efficiency of criminal case administration through file digitization, reduction of bureaucracy, and increased integration among law enforcement agencies.This research employs an empirical approach, utilizing qualitative data. Data were collected through both verbal and written interviews with judges, clerks, lawyers, bailiffs, and PTSP (One Stop Integrated Services) staff directly involved in the system's use, and the results were analyzed using information system implementation analysis theory and effectiveness theory. The findings indicate that the implementation of the E-Berpadu System at the Pontianak Class 1A District Court has significantly positive impacts. This system successfully accelerated the case administration process, improved data accuracy, and facilitated coordination between agencies. In addition, E-Berpadu also enhances transparency in the legal process by facilitating application submissions, electronic file transfers, and digital document management. However, there are several challenges faced, such as user adaptation to technology, data synchronization issues between institutions, and technical obstacles like unstable internet connections and a less user-friendly interface. This research recommends enhancing training and system development to address these challenges. Overall, E-Berpadu is considered effective in supporting the modernization of the criminal justice system at the Class 1A Pontianak District Court, although it still requires improvements in technological infrastructure and training support. This study makes an important contribution to the understanding of technology implementation in the judicial system and offers recommendations that can serve as a model for other courts in Indonesia.Keywords: District Court, E-Berpadu, Judicial modernization, Technological constraints, Effectiveness analysis  Abstrak  Penelitian ini bertujuan untuk menganalisis implementasi Sistem E-Berpadu (Elektronik Berkas Pidana Terpadu) di Pengadilan Negeri Pontianak Kelas 1A, yang merupakan inovasi digital Mahkamah Agung dalam rangka modernisasi sistem peradilan pidana. E-Berpadu dirancang untuk meningkatkan efisiensi administrasi perkara pidana melalui digitalisasi berkas, pengurangan birokrasi, dan peningkatan integrasi antar lembaga penegak hukumJenis penelitian ini adalah penelitian empiris. Data yang digunakan dalam penelitian ini adalah jenis data kualitatif. Data didapatkan dengan metode wawancara secara lisan maupun tertulis dengan hakim, panitera, pengacara, jurusita, serta staf ptsp yang terlibat langsung dalam penggunaan sistem dan hasilnya dianalisis dengan menggunakan teori analisis implementasi sistem informasi dan teori efektivitas.Hasil penelitian ini menunjukkan bahwa implementasi Sistem E-Berpadu di Pengadilan Negeri Pontianak Kelas 1A telah membawa dampak positif yang signifikan. Sistem ini berhasil mempercepat proses administrasi perkara, meningkatkan akurasi data, dan memudahkan koordinasi antar instansi. Selain itu, E-Berpadu juga meningkatkan transparansi dalam proses hukum dengan mempermudah pengajuan permohonan, pelimpahan berkas elektronik, dan pengelolaan dokumen secara digital. Namun, terdapat beberapa kendala yang dihadapi, seperti adaptasi pengguna yang belum terbiasa dengan teknologi, masalah sinkronisasi data antar lembaga, serta kendala teknis seperti koneksi internet yang tidak stabil dan antarmuka pengguna yang kurang ramah. Penelitian ini merekomendasikan peningkatan pelatihan dan pengembangan sistem untuk mengatasi tantangan tersebut. Secara keseluruhan, E-Berpadu dinilai efektif dalam mendukung modernisasi peradilan pidana di Pengadilan Negeri Pontianak Kelas 1A, meskipun masih memerlukan peningkatan infrastruktur teknologi dan dukungan pelatihan. Studi ini memberikan kontribusi penting terhadap pemahaman implementasi teknologi dalam sistem peradilan dan menawarkan rekomendasi yang dapat dijadikan model bagi pengadilan lain di Indonesia.Kata Kunci: Pengadilan Negeri, E-Berpadu, Modernisasi peradilan, Kendala teknologi, Analisis efektivitas